Expanding teff production: Economywide analysis of growth and poverty impacts - Benson, Todd; Legesse, Ermias Engida; Thurlow, James (International Food Policy Research Institute, 2018)
This chapter analyzes the economywide effects of significantly increasing the production of teff, wheat, and maize, both separately and jointly. Although our particular focus is on teff, maize and wheat are also considered closely in order to contrast the characteristics of teff and the other two cereals within the Ethiopian economy and for Ethiopian households. A detailed Computable General Equilibrium (CGE) model of the Ethiopian economy is used for this analysis. The CGE model is linked to a household survey–based microsimulation module. This enables estimation of the impact on household poverty and calorie intake of the various production scenarios run through the model. The production increases simulated in the analysis are consistent with the targets set by the Ethiopian Agricultural Transformation Agency (ATA) through their Teff, Wheat, and Maize Initiatives that began in 2012 and 2013. Accordingly, the simulation results provide additional evidence for evaluating Ethiopia’s cereals investment plan and the design of broader agricultural development strategy.